Bentuk dan Makna Nama-Nama Dusun di Kecamatan Nelle Kabupaten Sikka - Yosephus Dominikus Fernandez (Ranah: Jurnal Kajian Bahasa, 2022)
This study aims to describe the form, categorization, and meaning of the names of hamlets in the Nelle Subdistrict. The data in this study are the names of hamlets in Nelle Subdistrict, Sikka Regency. They were collected with the method of listening, recording and note-taking. The data is analyzed by using fixed comparison methods. The analysis of the data was presented with informal methods. The results of this study are as follows. The forms of the names of the hamlets consist of monomorphism and polymorphism. The names of the hamlets that include monomorphic are Enak, Detung, I, II, III, IV, Kode, Delang, Halat, Baluele, and Ritat. The hamlet’s name includes polymorphism, namely Koli Buluk, Tadabliro, Kloang Bola, Natar Lorong, Kloang Beit, Habipiret, and Keduwair. The categorization of the name of the hamlet in the Nelle Subdistrict is divided into aspects of embodiment and aspects of society. Aspects of embodiment are divided into several parts, namely location, geography, plants, water forms, and combinations. The name of the hamlet in the aspect of society is divided again in the aspect of nicknames. The name of the hamlet in another aspect, namely the number. The meaning of the name of the hamlet in the Nelle Subdistrict is divided into several types, such as lexical-grammatical, referential-nonrefferential, denotative-connotative, conceptual-associative, and word-terms. So, the name of the hamlet in the Nelle Subdistrict has a peculiarity that can be seen from its form, categorization, and meaning. AbstrakTujuan penelitian ini adalah mendeskripsikan bentuk, kategorisasi, dan makna nama-nama dusun di Kecamatan Nelle. Data dalam penelitian ini adalah nama-nama dusun di Kecamatan Nelle, Kabupaten Sikka. Data dikumpulkan menggunakan metode simak dengan teknik simak libat cakap, dan teknik lanjutannya ialah teknik rekam dan teknik catat. Data dianalisis dengan menggunakan metode perbandingan tetap. Hasil analisis data disajikan dengan metode informal. Hasil penelitian ini adalah sebagai berikut. Bentuk nama-nama dusun terdiri atas monomorfemis dan polimorfemis. Nama-nama dusun yang termasuk monomorfemis adalah Enak, Detung, I, II, III, IV, Kode, Delang, Halat, Baluele, dan Ritat. Nama dusun yang termasuk polimorfemis, yakni Koli Buluk, Tadabliro, Kloang Bola, Natar Lorong, Kloang Beit, Habipiret, dan Keduwair. Kategorisasi nama dusun di Kecamatan Nelle terbagi atas aspek perwujudan dan aspek kemasyarakatan. Aspek perwujudan terbagi dalam beberapa bagian, yakni letak, geografis, tanaman, wujud air, dan kombinasi. Nama dusun dalam aspek kemasyarakatan terbagi lagi dalam aspek julukan. Nama dusun dalam aspek lain, yakni jumlah. Makna nama dusun di Kecamatan Nelle terbagi dalam beberapa jenis, seperti makna leksikal-gramatikal, referensial-nonreferensial, denotatif-konotatif, konseptual-asosiatif, dan kata-istilah. Jadi, nama dusun di Kecamatan Nelle memiliki kekhasan yang dapat dilihat dari bentuk, kategorisasi, dan maknanya.